Penerapan Pendidikan Islam untuk Mengembangkan Akhlak Mulia pada Anak Usia Dini - Hasna Koba'a; Sahrul Salingkat; Tri Endang Jatmikowati (Fakultas Agama Islam Universitas Muhammadiyah Luwuk, 2024)
The use of storytelling or habituation techniques in Islamic early childhood education (PAUD), especially in institutions such as PAUD Al Hasanah Luwuk, is still fairly minimal. This study aims to analyse the application of Islamic education in developing noble morals in early childhood at PAUD Al Hasanah Luwuk. The scope of the study includes aspects of teaching morals based on Islamic teachings through learning methods applied in these educational institutions. The purpose of this research is to find out how Islamic education is applied in shaping children's noble character and morals, as well as to evaluate its impact on their moral development. The method used in this research is a qualitative approach with a case study type. Data collection was conducted through direct observation, interviews with educators and parents, as well as documentation of activities conducted at PAUD Al Hasanah Luwuk. The results showed that Islamic education at PAUD Al Hasanah Luwuk includes teaching about moral values contained in Islamic teachings, such as discipline, compassion, honesty, and courtesy. The use of storytelling methods, joint prayers, and daily activities based on Islamic values proved effective in developing noble morals in early childhood. The conclusion of this study is that the consistent implementation of Islamic education can play an important role in shaping the noble morals of early childhood, which will have a positive impact on their moral development in the future